2010
DOI: 10.1016/j.molcel.2010.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of the TRAF2: cIAP2 and the TRAF1: TRAF2: cIAP2 Complexes: Affinity, Specificity, and Regulation

Abstract: SUMMARY TRAF1/2 and cIAP1/2 are members of the TNF receptor associated factor (TRAF) and the inhibitor of apoptosis (IAP) families, respectively. They are critical for both the canonical and the noncanonical NF-κB signaling pathways. Here we report the crystal structures of the TRAF2: cIAP2 and the TRAF1: TRAF2: cIAP2 complexes. A TRAF2 trimer interacts with one cIAP2 both in the crystal and in solution. Two chains of the TRAF2 trimer directly contact cIAP2 and key residues at the interface are confirmed by mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
202
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(215 citation statements)
references
References 44 publications
10
202
3
Order By: Relevance
“…Indeed, this would explain why WT and cIAP1 Ϫ/Ϫ CD8 T cells do not require the noncanonical NF-B pathway when 4-1BB costimulation is present, but TRAF1 Ϫ/Ϫ T cells do. Whereas the present study shows that TRAF1 is critical to prevent NIK activation in activated T cells, Zheng et al did not observe constitutive processing of p100 to p52 in TRAF1 Ϫ/Ϫ -resting B cells (47). As resting B cells, and in fact most nonlymphoid cells, lack detectable TRAF1 (58), the regulation of NIK in resting primary B cells and other cell types could not involve TRAF1 or these cells would show constitutive alternative NF-B activation.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Indeed, this would explain why WT and cIAP1 Ϫ/Ϫ CD8 T cells do not require the noncanonical NF-B pathway when 4-1BB costimulation is present, but TRAF1 Ϫ/Ϫ T cells do. Whereas the present study shows that TRAF1 is critical to prevent NIK activation in activated T cells, Zheng et al did not observe constitutive processing of p100 to p52 in TRAF1 Ϫ/Ϫ -resting B cells (47). As resting B cells, and in fact most nonlymphoid cells, lack detectable TRAF1 (58), the regulation of NIK in resting primary B cells and other cell types could not involve TRAF1 or these cells would show constitutive alternative NF-B activation.…”
Section: Discussioncontrasting
confidence: 81%
“…A recent study using an overexpression system, reported that TRAF1 and TRAF2 can be pulled down with TAP tagged NIK, suggesting that TRAF1 like TRAF2 might be part of the E3 complex for NIK (47). Here we have unconvered a hitherto unrecognized role for TRAF1 in contributing to inhibition of the non-canonical NF-B pathway in TCR-activated CD8 T cells.…”
Section: Discussionmentioning
confidence: 51%
“…This suggests that upon TNF stimulation cIAP1 is recruited to receptor complexes by TRAF2, and cIAP1 dimerization is promoted. Recently, it has been shown that the TRAF2 trimer only binds to a single cIAP protein (51,52); therefore, cIAP dimer formation is likely to require the interaction of cIAP molecules bound to two TRAF2 trimers. Whether two separate TNFR1-TRADD complexes recruit two TRAF2 trimers or whether the cIAP RING dimer is sufficient to facilitate cIAP1/TRAF2 recruitment without the involvement of another receptor is an interesting question.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] The E3 ubiquitin ligase TRAF2 was the first to be described as being responsible for K63 ubiquitination of RIP1 [5][6][7] together with the lipid shingosine-1-phosphate. 8 Other publications have shown that cIAP1/2 can attach K63 ubiquitin chains to RIP1 [9][10][11][12] or that TRAF2 and cIAPs cooperate for the ubiquitination of RIP1 6,13,14 . These ubiquitin chains bind and associate the TAB/TAK (TAK1/TAB2/TAB3) and NEMO/IKK (IKKa, b, g) kinases complex.…”
mentioning
confidence: 99%